Heterotrophic Bacteria Exhibit a Wide Range of Rates of Extracellular Production and Decay of Hydrogen Peroxide - Bond, Robin J.; Hansel, Colleen M.; Voelker, Bettina M. (Frontiers in Marine Science, 2020)
Bacteria have been implicated as both a source and sink of hydrogen peroxide (H2O2), a reactive oxygen species which can both impact microbial growth and participate in the geochemical cycling of trace metals and carbon in natural waters. In this study, simultaneous H2O2 production and decay by twelve species of heterotrophic bacteria were evaluated in both batch and flow-through incubations. While wide species-to-species variability of cell-normalized H2O2 decay rate coefficients [2x10-8 to 5x10-6 hr-1 (cell mL-1)-1] was observed, these rate coefficients were relatively consistent for a given bacterial species. By contrast, observed production rates (below detection limit to 3x102 amol cell-1 hr-1) were more variable even for the same species. Variations based on incubation conditions in some bacterial strains suggest that external conditions may impact extracellular H2O2 levels either through increased extracellular production or leakage of intracellular H2O2. Comparison of H2O2 production rates to previously determined O2- production rates suggests that O2- and H2O2 production are not necessarily linked. Rates measured in this study indicate that bacteria could account for a majority of H2O2 decay observed in aqueous systems but likely only make a modest contribution to dark H2O2 production.